Assessment of local supply chains and stock management practices for trauma care resources in Ghana: a comparative small sample cross-sectional study - Godfred Boakye; Adam Gyedu; Melissa Stewart; Peter Donkor; Charles Mock; Barclay Stewart (BMC, 2021)
Abstract Background Injuries are a major public health problem globally. With sound planning and organization, essential trauma care can be reliably provided with relatively low-cost equipment and supplies. However, availability of these resources requires an effective and efficient supply chain and good stock management practices. Therefore, this study aimed to assess trauma care resource-related supply management structures and processes at health facilities in Ghana. By doing so, the findings may allow us to identify specific structures and processes that could be improved to facilitate higher quality and more timely care. Methods Ten hospitals were purposively selected using results from a previously performed national trauma care capacity assessment of hospitals of all levels in Ghana. Five hospitals with low resource availability and 5 hospitals with high resource availability were assessed using the United States Agency for International Development (USAID) Logistics Indicators Assessment Tool and stock ledger review. Data were described and stock management practices were correlated with resource availability. Results There were differences in stock management practices between low and high resource availability hospitals, including frequency of reporting and audit, number of stock-outs on day of assessment (median 9 vs 2 stock-outs, range 3-57 vs 0-9 stock-outs, respectively; p = 0.05), duration of stock-outs (median 171 vs 8 days, range 51-1268 vs 0-182 days, respectively; p = 0.02), and fewer of up-to-date stock cards (24 vs 31 up-to-date stock cards, respectively; p = 0.07). Stock-outs were common even among low-cost, essential resources (e.g., nasal cannulas and oxygen masks, endotracheal tubes, syringes, sutures, sterile gloves). Increased adherence to stock management guidelines and higher percentage of up-to-date stock cards were correlated with higher trauma resource availability scores. However, the variance in trauma resource availability scores was poorly explained by these individual factors or when analyzed in a multivariate regression model (r2 = 0.72; p value for each covariate between 0.17-0.34). Conclusions Good supply chain and stock management practices are correlated with high trauma care resource availability. The findings from this study demonstrate several opportunities to improve stock management practices, particularly at low resource availability hospitals.